Peningkatan Aktivitas Belajar Siswa melalui Layanan Informasi Cara Belajar Efektif - Azam Arifyadi; Mardi Lestari; Moh. Dayan (Universitas Tadulako, 2021)
This research was motivated by the low learning activity of students at school. The main objective of this research was to explain the positive effect of information services on effective learning methods in increasing student learning activities. Subjects in this study were 28 students. the instrument used to collect data was a student learning activity questionnaire. The data obtained were then analyzed descriptively and inferentially. Hypothesis testing using statistical techniques was the t-test (one tail) at a significant level of 95%. The results of the descriptive analysis showed that student learning activities before being provided with information services on effective learning methods at school were 3.57% students who have high learning activities, 85.7% students who have low learning activities, 10.7% students who have very low learning activities. Meanwhile, after being provided with services for effective learning methods at school, there were 7.14% of students who have very high learning activities, 60.71% of students who have high learning activities, 32.14% of students who have low learning activities. From the results of the inferential analysis showed that there was an effect of information services on effective learning methods in increasing the learning activities of class X SMA Negeri 1 Ampibabo students.